IoT based Kit for Medication Monitoring - N., Asha C; P., Yashawini; P., Pranathi M; G., Sneha N; Akshaya, Veerapureddy (IRO Journal on Sustainable Wireless Systems, 2025)
Medication non-adherence remains a significant challenge in healthcare, leading to suboptimal patient outcomes and increased medical expenditures. This study introduces an innovative Internet of Things (IoT)-based kit designed to monitor medication adherence. The proposed kit employs various sensors to ensure precise tracking and supervision of medication intake. Its seamless integration with a cloud platform facilitates remote access, real-time data processing, and storage. Through an intuitive mobile application or web interface, users receive personalized notifications and reminders to assist them in adhering to their medication schedules. Furthermore, the kit offers historical data tracking, enabling both users and healthcare professionals to assess adherence trends over time. This IoT-based medication monitoring kit provides a connected and intelligent approach to optimizing medication management in contemporary healthcare settings, thereby enhancing health outcomes and improving patient care. It represents a promising solution to the issue of medication non-adherence.
Keywords: IoT; IR Sensor; Arduino UNO; Telegram App